P2.049 NAATs For Gonorrhoea Diagnosis in Women: Experience of a Tertiary Care Hospital in North India. (13th July 2013) - Sood, S; Verma, R; Mir, S; Agarwal, M; Singh, N; Kar, H K; Sharma, V K
Abstract : Background: Gonorrhoea is among the most frequent of the estimated STIs and health implications related to morbidity and mortality especially in women and children are significant. The use of nucleic acid amplification tests (NAATS) has been shown to provide enhanced diagnosis of gonorrhoea in female patients & are considered the standard for diagnostic purposes currently. However, it is recommended that an on-going assessment of the test assays should be performed to check for any probable sequence variation occurring in the targeted region. In the present study, an in-house PCR targeting opa -gene of Neisseria gonorrhoeae was used in conjunction with 16S ribosomal PCR to determine the prevalence of gonorrhoea in female patients attending the tertiary care hospitals Methods: Endocervical samples collected from 250 female patients attending the Dermatology and Gynaecology OPD of AIIMS and STD clinic of Dr. R.M.L. Hospital, New Delhi, India were tested using opa and 16S ribosomal assay. Additionally, they were processed by conventional methods. True positives were defined as ones which were positive by culture and/or positive by both 16S ribosomal gene and opa- gene based PCR. Results: Of the 250 female patients, only 1 was positive by conventional methods, i.e., microscopy and culture. Based on PCR results, opa- gene based PCR was positive in 17 patients who were also positive by 16S ribosomal PCR. However, 16S ribosomal gene based PCR picked up 8 extra positives. Overall, 17 patients were found to be true positives. Conclusion: The clinical sensitivity of conventional methods for the detection of N. gonorrhoeae in female patients is low. The gonococcal detection rates increased significantly when molecular method was used giving a prevalence rate of 6.8%. However, it is pertinent to mention that the widespread use of NAATs might result in lack of isolates and ignorance of possible emergence of resistant organisms.